Importance of microalgae and municipal waste in bioenergy products hierarchy—integration of biorefineries for microalgae and municipal waste processing : A review - Kim, Kate; Hourfar, Farzad; Abdul Halim, Abdul Razik; Rizwan, Muhammad; Almansoori, Ali; Fowler, Michael W.; Elkamel, Ali (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
In the context of global advancements, the imperative of a sustainable energy supply looms large. Biomass, an adaptable and renewable resource, has garnered attention for its potential contributions, although economic uncertainties persist due to the intricate web of processing pathways. In response, the biorefinery concept emerges as a structured strategy to optimize the processing of microalgae and municipal solid waste (MSW), capitalizing on their multifaceted potential to yield diverse end-products. This review underscores the critical significance of a cohesive biorefinery paradigm that unites the processing of microalgae and MSW, unveiling their capacity to generate a spectrum of high-value products. The utilization of mixed-integer linear programming paves the way for an optimal biorefinery model that navigates through complex decisions. Challenges encompass the array of diverse feedstocks and the preliminary nature of data availability. The overarching goal of this research is to discern optimal pathways for the conversion of MSW and microalgae into energy and valuable products, with a focus on enhancing waste utilization and augmenting the energy supply. In the broader landscape, this comprehensive review advances strategies for sustainable energy generation and waste management, invigorating innovative approaches to shape future progress. By illuminating pathways towards maximizing the potential of biomass resources, this review contributes to the ongoing discourse on sustainable energy and waste utilization.